2015
DOI: 10.1680/warm.14.00021
|View full text |Cite
|
Sign up to set email alerts
|

Waste-derived activated carbons for control of nitrogen oxides

Abstract: Activated carbons were produced from waste and investigated for their efficiency for the removal of mono-nitrogen oxides (NO x ) in simulated flue gases at a low temperature. The wastes used were waste biomass (date seeds), processed municipal solid waste in the form of refuse-derived fuel and waste tyres. The morphology, porous texture and surface chemistry of the prepared activated carbons were evaluated by scanning electron microscopy, energydispersive X-ray spectrometry, nitrogen adsorption and Boehm titra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The elemental compositions of the catalysts are summarized in Table 2. PKS exhibits a high carbon content (82%), comparable with commercial activated carbons [29]. After metal impregnation the C:H ratio significantly increased suggesting that the presence of the metal catalyses the carbonisation of the PKS.…”
Section: Catalyst Characterisationmentioning
confidence: 83%
“…The elemental compositions of the catalysts are summarized in Table 2. PKS exhibits a high carbon content (82%), comparable with commercial activated carbons [29]. After metal impregnation the C:H ratio significantly increased suggesting that the presence of the metal catalyses the carbonisation of the PKS.…”
Section: Catalyst Characterisationmentioning
confidence: 83%
“…Biomass waste in the form of agricultural waste materials have been extensively investigated as precursors for the production of activated carbons (Yahya et al, 2015, Koseoglu andAkmil-Basar, 2015;Ioannidou and Zabaniotou, 2007). For example, cotton stalks (Nahil and Williams, 2012) date stones (Al-Rahbi et al, 2016), coconut shell (Hu and Srinivasan, 1999) palm shell (Daud et al, 2000) rice bran (Suzuki et al, 2007), corn cobs (El-Hendawy et al, 2001) rice husks (Yalcin and Sevine, 2000) etc.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorptive properties of such waste derived activated carbons have been utilised as pollution control materials for control of polluting gases. For example, Al-Rahbi et al (2016) used waste biomass in the form of date stones to produce activated carbons for the low temperature (50 °C) control of NOx. They reported that the biomass derived activated carbon had similar removal efficiencies for NOx as for commercially available activated carbons and that the micropore structure of the carbon significantly influences removal efficiency.…”
Section: Introductionmentioning
confidence: 99%